Monitoring parotid gland tumors with a new perfusion software for contrast-enhanced ultrasound - Klotz, Laura Valentina; Ingrisch, Michael; Eichhorn, Martin E.; Niemoeller, Olivier; Siedek, Vanessa; Gürkov, Robert; Clevert, Dirk-Andre (Clinical hemorheology and microcirculation, 2014)
PURPOSE: Contrast enhanced ultrasound (CE-US) is a promising imaging modality for non-invasive analysis of functional vascularisation. Lesions of the parotid gland are associated with a vascularisation that differs from normal gland tissue. The aim o